Bilateral leiomyoma in the testes of a horse. (24th November 2014) - Stoll, A. L.; Tucker, R.; Witte, T. H.; Smith, K. C.
Summary A 19‐year‐old Hackney pony was referred to a veterinary teaching hospital for further investigation of left‐sided scrotal enlargement. Both testes were normally positioned within the scrotum and there was no pain on palpation. Ultrasonography revealed multiple masses of soft tissue echogenicity, located adjacent to the testicular parenchyma. They were hyperechoic when compared to the testicular parenchyma and affected both testes. Surgical excision was performed by closed castration. Gross examination revealed firm, white, nodular masses of varying size on the surface of both testes. The cut surface of individual masses had a dense, whorling, fibrous and somewhat shiny appearance. The histopathological diagnosis was bilateral, multicentric, well differentiated leiomyoma of the tunica albuginea. The smooth muscle origin was confirmed by immunohistochemical staining with an anti‐human monoclonal antibody reactive to smooth muscle actin. This is the first report of a bilateral, multicentric, leiomyoma in the testes of a horse confirmed by histopathology and immunohistochemistry. This case highlights that neoplasia should be considered as a differential for bilateral testicular enlargement.